INFORMATION BULLETIN «NEW METHODOLOGIES RECOMMENDED FOR INTEGRATION INTO THE SERVICES PERFORMED BY FORENSIC SCIENCE ORGANIZATIONS OF THE RUSSIAN MINISTRY OF JUSTICE» (Issue 37) - N. Monina (Теория и практика судебной экспертизы)
.